Continuous Fabrication of Meter‐Scale Single‐Wall Carbon Nanotube Films and their Use in Flexible and Transparent Integrated Circuits. Issue 32 (27th June 2018) - Wang, Bing‐Wei; Jiang, Song; Zhu, Qian‐Bing; Sun, Yun; Luan, Jian; Hou, Peng‐Xiang; Qiu, Song; Li, Qing‐Wen; Liu, Chang; Sun, Dong‐Ming; Cheng, Hui‐Ming
Abstract: Single‐wall carbon nanotubes (SWCNTs), especially in the form of large‐area and high‐quality thin films, are a promising material for use in flexible and transparent electronics. Here, a continuous synthesis, deposition, and transfer technique is reported for the fabrication of meter‐scale SWCNT thin films, which have an excellent optoelectrical performance including a low sheet resistance of 65 Ω/◽ with a transmittance of 90% at a wavelength of 550 nm. Using these SWCNT thin films, high‐performance all‐CNT thin‐film transistors and integrated circuits are demonstrated, including 101‐stage ring oscillators. The results pave the way for the future development of large‐scale, flexible, and transparent electronics based on CNT thin films. Abstract : Meter‐scale single‐wall carbon nanotube (SWCNT) thin films with an excellent optoelectrical performance and uniformity are produced by a continuous growth, deposition, and transfer technique. Using these SWCNT thin films, highly flexible and transparent all‐CNT TFTs and ICs including 101‐stage ring oscillators are constructed and show excellent performance.